Parenteral 1, 25-dihydroxycholecalciferol in hepatic osteomalacia. Issue 6105 (14th January 1978) - Long, R G; Varghese, Z; Meinhard, E A; Skinner, R K; Wills, M R; Sherlock, S
Abstract : Despite regular long-term parenteral vitamin D2 treatment, four patients with biliary cirrhosis had multiple symptoms of bone disease and bone biopsy specimens showed osteomalacia without osteoporosis. Three patients also had a proximal myopathy. Plasma calcium values (after correction for albumin), phosphorus, magnesium, and serum 25-hydroxy-vitamin D were within normal limits. Treatment with 1, 25-dihydroxy-cholecalciferol (1, 25-(OH)2D3) relieved symptoms in three of the four patients and improved those in the fourth. Histological examination of bone showed improvement in all four patients, but serum and urinary biochemical changes were not pronounced. We conclude that 1, 25-(0H)2D3 treatment has a beneficial effect on bone and muscle in hepatic osteomalacia, either because vitamin D 1-hydroxylation fails in biliary cirrhosis or because hepatic osteomalacia is resistant to vitamin D2 metabolites.